Characterization of the dynamics of interfaces and of interface-dominated systems via spectroscopy and microscopy techniques. (September 2018) - Cristofolini, Luigi; Orsi, Davide; Isa, Lucio
Abstract: Complex interfaces, such as vesicles and biological membranes, and interface-dominated systems, such as foams and emulsions, are central to a vast range of naturally occurring and synthetic materials. In order to characterize their dynamics, it is necessary to cover a wide range of length and time scales. This can only be done by a combination of different techniques. We review here recent results and discuss new trends focusing on two class of techniques: correlation spectroscopies and microscopies, highlighting some examples of their combined use. Graphical abstract: Unlabelled Image Highlights: In complex interfaces and interface-dominated systems, dynamics impact a wide range of technologies. To characterize dynamics, a combination of techniques spanning a large range of space and time scales is needed. Synergy between microscopy, direct accessing dynamics, and spectroscopy, which is superior in terms of statistics. New results expected from the application of optical Monte Carlo methods to DWS. New results expected from upcoming coherent x-ray beams (upgraded synchrotrons, XFELs) accessing fast dynamics. A wealth of new microscopy techniques recently developed, thanks to new fast image processing hardware and software.